Cost-effectiveness of empagliflozin in patients with type 2 diabetes and established cardiovascular disease in China - Mafalda Ramos (Cost Effectiveness and Resource Allocation, 2021)
Abstract Background In several cardiovascular outcome trials (CVOTs), empagliflozin (SGLT-2 inhibitor), sitagliptin (DPP-4 inhibitor) and liraglutide (GLP-1 receptor agonist) + standard of care (SoC) were compared to SoC in patients with type 2 diabetes and established cardiovascular disease (CVD). This study assessed the cost-effectiveness (CE) of empagliflozin + SoC in comparison to sitagliptin + SoC and liraglutide + SoC based on the respective CVOT. Methods The IQVIA Core Diabetes Model (CDM) was calibrated to reproduce the CVOT outcomes. EMPA-REG OUTCOME baseline characteristics and CVOT specific treatment effects on risk factors for cardiovascular disease (HbA1c, BMI, blood pressure, lipids) were applied. Three-year observed cardiovascular events of empagliflozin + SoC versus sitagliptin + SoC and liraglutide + SoC were derived from EMPA-REG OUTCOME and an indirect treatment comparison. Relative risk adjustments to calibrate the CDM were obtained after a trial and error process to match as closely the observed and CDM-predicted outcomes. The drug-specific treatment effects were considered up until HbA1c reached 8.5% and treatment switch occurred. After this switch, the United Kingdom Prospective Diabetes Study 82 risk equations predicted events based on co-existing risk factors and treatment intensification to basal bolus insulin were applied. The analysis was conducted from the perspective of the Chinese healthcare system applying 3% discounting. The time horizon was lifelong. Results Empagliflozin + SoC provides additional Quality Adjusted Life years (QALY + 0.564) for an incremental cost of 42,497RMB (US$6053) compared to sitagliptin + SoC, resulting in an Incremental Cost Utility Ratio of 75,349RMB (US$10,732), thus below the willingness-to-pay threshold of 212,676RMB, corresponding to three times the Gross Domestic Product in China (2019). Compared to liraglutide + SoC, empagliflozin + SoC use leads to 0.211QALY gained and cost savings of 71,427RMB (US$10,173) and is as such dominant. Scenario and probabilistic sensitivity analyses demonstrated the robustness of the results. Conclusion Results suggest that empagliflozin + SoC is cost-effective compared to sitagliptin + SoC and liraglutide + SoC at a willingness-to-pay threshold of 212,676RMB ($30,292)/QALY.